(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was carried out on 105 pregnant women with preeclampsia in addition to 105 pregnant women without preeclampsia as a control at Al-Najaf province from September ,2017-May 2018. All the included patients were examined by Doppler study to assess the resistive index of umbilical artery RI in preeclamptic pregnant patients with PE and pregnant women without PE. The results reveals that there was significant difference of umbilical artery RI 0.658±0.304, concerning preeclamptic pregnant patients in comparison to pregnant women without PE(0.571±0.215) , ( PV lesser than0.05) . In addition to that the umbilical artery RI was (0.577±0.301) in preeclamptic pregnant patient with mild PE while it was (0.813±0.247) in preeclamptic pregnant patient with severe PE which displayed a statistically significant difference( PV less than0.05).Also this study showed that the umbilical artery RI in preeclamptic pregnant patients with H. pylori was(1.11±0.319) which was greater than that for preeclamptic pregnant patients without H. pylori (0.919±0.25) with a statistically significant difference ( PV less than 0.5). It was concluded that Umbilical artery resistive index is a useful parameter in detection of preeclampsia and its severity and the umbilical artery resistive index might be useful parameter in prediction of infection of positive H. pylori infection associated with preeclampsia.